Catechols and 3-hydroxypyridones as inhibitors of the DNA repair complex ERCC1-XPF. Issue 19 (1st October 2015) - Chapman, Timothy M.; Gillen, Kevin J.; Wallace, Claire; Lee, Maximillian T.; Bakrania, Preeti; Khurana, Puneet; Coombs, Peter J.; Stennett, Laura; Fox, Simon; Bureau, Emilie A.; Brownlees, Janet; Melton, David W.; et al.
Graphical abstract